A microgroove patterned multiwell cell culture plate for high‐throughput studies of cell alignment. Issue 12 (29th July 2014) - Lücker, Petra B.; Javaherian, Sahar; Soleas, John P.; Halverson, Duncan; Zandstra, Peter W.; McGuigan, Alison P.
ABSTRACT Grooved substrates are commonly used to guide cell alignment and produce in vitro tissues that mimic certain aspects of in vivo cellular organization. These more sophisticated tissues provide valuable in vitro models for testing drugs and for dissecting out molecular mechanisms that direct tissue organization. To increase the accessibility of these tissue models we describe a simple and yet reproducible strategy to produce 1 µm‐spaced grooved well plates suitable for conducting automated analysis of cellular responses. We characterize the alignment of four human cell types: retinal epithelial cells, umbilical vein endothelial cells, foreskin fibroblasts, and human pluripotent stem‐cell‐derived cardiac cells on grooves. We find all cells align along the grooves to differing extents at both sparse and confluent densities. To increase the sophistication of in vitro tissue organization possible, we also created hybrid substrates with controlled patterns of microgrooved and flat regions that can be identified in real‐time using optical microscopy. Using our hybrid patterned surfaces we explore: (i) the ability of neighboring cells to provide a template to organize surrounding cells that are not directly exposed to grooved topographic cues, and (ii) the distance over which this template effect can operate in confluent cell sheets. We find that in fibroblast sheets, but not epithelial sheets, cells aligned on grooves can direct alignment of neighboring cells in flat regions over a limited distance of approximately 200 μm. Our hybrid surface plate provides a novel tool for studying the collective response of groups of cells exposed to differential topographical cues. Biotechnol. Bioeng. 2014;111: 2537–2548. © 2014 Wiley Periodicals, Inc.